Effectiveness of training program on the knowledge of midwifes and nursing responsibilities Post Blood Transfusion at Nasser medical complex, Palestine - Taghreed Mohammed Abu hadaf, Taghreed; Al-Dar, Mohammed Jabr (International Journal of Nursing and Health Services (IJNHS), 2025)
Blood transfusion is a crucial procedure in medical care, especially in obstetrics and emergencies, where strict adherence to protocols is essential to avoid severe complications. This study assesses the impact of a targeted training program on midwives and nurses at Nasser Medical Hospital in Palestine, focusing on essential post-transfusion nursing responsibilities. The program aimed to enhance critical skills, including patient identification, blood product verification, and risk management, addressing key knowledge gaps in healthcare practice. Using a Randomized Controlled Trial (RCT) design, 45 midwives and nurses were randomly chosen to participate. Data collected through structured questionnaires were analyzed with SPSS to evaluate knowledge levels before and after training. The participant cohort, predominantly female (84.4%) and largely aged 35-40 years (42.2%), is primarily composed of professionals holding a Bachelor’s degree (77.8%). Participants represent diverse roles, with midwives (57.8%) and nurses (42.2%) from departments such as the Labor and Delivery Ward (46.7%), Cesarean Section Operations (28.9%), and Neonatal and Maternity Department ((24.4%). The training program led to significant improvements in knowledge scores related to post-transfusion complications, with a mean increase from 76.71 to 96.81 (MD = 20.10, P < 0.001). This improvement was consistent across various demographics, including gender, age, education, marital status, professional experience, and department. For instance, participants over 40 years achieved the highest effect size (2.27), and diploma holders displayed the greatest mean difference (28.99). Additionally, both midwives and nurses saw substantial knowledge gains, with the Cesarean Section Operations and Neonatal and Maternity Departments exhibiting the highest improvements. These findings underscore the program's broad efficacy in enhancing transfusion-related knowledge, reinforcing its value in promoting patient safety and care quality at the ComplexThe study recommends expanding targeted training to include other healthcare professionals, conducting long-term evaluations, incorporating simulation-based learning, and analyzing patient outcomes. It suggests broader implementation in diverse settings, tailoring content to specific roles, and addressing psychological readiness to enhance skills, promote safety, and improve transfusion practices in clinical care